2021
DOI: 10.1126/sciadv.abb4644
|View full text |Cite
|
Sign up to set email alerts
|

Diamond formation in an electric field under deep Earth conditions

Abstract: Most natural diamonds are formed in Earth’s lithospheric mantle; however, the exact mechanisms behind their genesis remain debated. Given the occurrence of electrochemical processes in Earth’s mantle and the high electrical conductivity of mantle melts and fluids, we have developed a model whereby localized electric fields play a central role in diamond formation. Here, we experimentally demonstrate a diamond crystallization mechanism that operates under lithospheric mantle pressure-temperature conditions (6.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Classic models of diamond formation by, for example, oxidized fluids or melts interacting with reduced (but metal-free) mantle, or vice-versa, remain elusive to test experimentally. Other models, such as diamond formation by decompression or cooling of fluids (Stachel and Luth 2015), by partial melting in the presence of a hydrous, carbon-bearing fluid (Luth 2017;Smit et al 2019), by pH changes in a fluid interacting with different mantle lithologies (Sverjensky and Huang 2015), under the influence of an electric field (Palyanov et al 2021b), or by mixing of different fluids or melts (e.g., Huang and Sverjensky 2020) await experimental testing as well. There are still many experiments to perform to understand the growth of super deep diamonds in the transition zone and lower mantle.…”
Section: Studymentioning
confidence: 99%
“…Classic models of diamond formation by, for example, oxidized fluids or melts interacting with reduced (but metal-free) mantle, or vice-versa, remain elusive to test experimentally. Other models, such as diamond formation by decompression or cooling of fluids (Stachel and Luth 2015), by partial melting in the presence of a hydrous, carbon-bearing fluid (Luth 2017;Smit et al 2019), by pH changes in a fluid interacting with different mantle lithologies (Sverjensky and Huang 2015), under the influence of an electric field (Palyanov et al 2021b), or by mixing of different fluids or melts (e.g., Huang and Sverjensky 2020) await experimental testing as well. There are still many experiments to perform to understand the growth of super deep diamonds in the transition zone and lower mantle.…”
Section: Studymentioning
confidence: 99%
“…It can reduce the nucleation time, control the location of nucleation, crystal orientation, and polymorphism. 36 A very recent work by Palyanov et al 37 has indicated that electric fields are key additional factor influencing diamond crystallization in the Earth lithospheric mantle. Moreover, referring to a previous study by Esrafilzadeh et al , 10 on the production of amorphous solid carbon at room temperature via CO 2 RR using liquid metals featuring atomically thin ceria interfaces, the liquid metal is highly conductive and is suitable for electrochemical redox processes.…”
Section: Resultsmentioning
confidence: 99%
“…Redox freezing is a well-known example of reactive preservation, where carbonatitic melt is reduced by metallic iron to form immobile diamond or iron carbide (Palyanov et al, 2013;Rorhbach & Schmidt, 2011). Decomposition of siderite FeCO 3 melt at high temperature can also change carbon into the native element state (Kang et al, 2015).…”
Section: Reactive Preservation Of Carbonatementioning
confidence: 99%
“…The efficiency of carbonate retention in the MTZ thus depends on how rapidly Ca-carbonate converts to the more refractory magnesite before slabs warm up sufficiently to induce melting. The extent of carbonate retention is further complicated by other processes such as reverse conversion of magnesite to Ca-Na-rich carbonate (Grassi & Schmidt 2011;Thomson et al, 2016) and reduction of magnesite into elemental carbon or iron carbides (Palyanov et al, 2013). A reliable assessment of carbonate stability in the MTZ thus requires quantifying the effects of water and temperature on the rates of these reactions.…”
Section: Implications For Deep Carbon Cyclementioning
confidence: 99%